TIMP-1 in the prognosis of patients who underwent coronary artery bypass surgery: a 12-year follow-up study - Huang, Jui-Tzu; Sung, Shih-Hsien; Hsu, Chiao-Po; Chiang, Chern-En; Yu, Wen-Chung; Cheng, Hao-Min; Huang, Cheng-Hsiung (Frontiers in Cardiovascular Medicine, 2023)
Introduction Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been linked to clinical outcomes in patients with coronary artery disease (CAD). However, the prognostic value of TIMP-1 in patients with CAD who underwent coronary artery bypass grafting (CABG) has not been elucidated. We aimed to investigate the correlations of TIMP-1 with high-sensitivity C-reactive protein (hs-CRP) and N-terminal pro-brain natriuretic peptide (NT-proBNP) in the long-term prognosis of consecutive patients who underwent CABG. Methods A total of 234 patients (age: 70.4 ± 10.5 years, 84.6% men) with CAD who underwent CABG were prospectively enrolled. Preoperative levels of MMPs, TIMP-1, hs-CRP, and NT-proBNP were recorded. Major adverse cardiovascular events (MACE) were defined as non-fatal myocardial infarction, non-fatal stroke, and cardiovascular death. Results During a median follow-up of 12.1 years, 120 deaths were recorded. The deceased were older, had more manifest acute coronary syndrome (ACS), a lower left ventricular ejection fraction (LVEF), and an estimated glomerular filtration rate (eGFR), but significantly higher MMP13, TIMP-1, hs-CRP, and NT-proBNP compared with the survivors. After adjusting for age, sex, manifest ACS, eGFR, LVEF, total cholesterol, and triglycerides, TIMP-1 (hazard ratio and 95% confidence intervals per SD: 1.506, 1.183–1.917), hs-CRP (1.349, 1.183–1.561), and NT-ProBNP (1.707, 1.326–2.199) were all independently associated with all-cause mortality. The mediation analysis revealed that the mortality risks of TIMP-1 were partially mediated by NT-proBNP (62.2%) and hs-CRP (25.3%). The associations of TIMP-1 with MACE were partially mediated by NT-proBNP (54.4%) but not hs-CRP. Conclusions TIMP-1 was an independent predictor of long-term outcomes after CABG, with possible roles in subclinical inflammation and postoperative cardiac remodeling.